Analisis Efektivitas Pengelolaan Dan Sistem Pengendalian Piutang Pada CV. Parulian Sojuangon Panggabean Group Kabupaten Tapanuli Tengah - Indah Gusmaini Lubis; Yenni Sofiana Tambunan; Safriadi Pohan (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2024)
This research aims to determine the influence of leadership style and work environment on employee performance at the Sibolga Pratama Tax Service Office. The population and sample for this research were all 106 civil servant employees at the Sibolga Primary Tax Service Office. The research method used is a quantitative research method with a descriptive approach. The data collection technique is a questionnaire using a Likert scale, while the tests used are the Classic Assumption Test and Analysis Test. The results of the research show that the performance of Receivable Turn Over (RTO) fluctuates from year to year. The highest increase in RTO occurred in 2019 at 4.16 times. The company's Average Collection Period (ACP) level was the best in 2019, namely 87 days, where the receivables turnover rate was very high. In 2019 the company's performance improved, where the arrears ratio reached its smallest point, namely 16.20%. In 2019 the performance of CV. Parulian Sojuangon Panggabean Group experienced an increase, where the collection ratio reached its highest point, namely 83.79%.